Heavenly journeys, earthly concerns : the legacy of the miʻraj in the formation of Islam - Vuckovic, Brooke Olson (Religion in history, society & culture, 2005)
Examines how an elite group of traditionists, historians and theologians shaped Muslims' perceptions of their prophet, their community and their behaviour by retelling and interpreting the story of Muhammad's ascent to heaven (the mi'raj).